APLIKASI DOA SEHARI HARI UNTUK UMAT MUSLIM BERBASIS ANDROID STUDIO - Randi Andika; Muhammad Ihsan (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
In the context of Islam, prayer plays a central role in the daily lives of Muslims. Prayer serves not only as a means to seek protection or request needs but also as a form of worship and direct communication with Allah. This study develops an application called